2006
DOI: 10.1590/s0080-62342006000300017
|View full text |Cite
|
Sign up to set email alerts
|

A regulação das relações de trabalho e o gerenciamento de recursos humanos em enfermagem

Abstract: Este artigo tem a finalidade de discorrer sobre a regulação das relações de trabalho na enfermagem, subsidiando a prática gerencial do enfermeiro, no que se refere aos direitos e obrigações de empregados e empregadores, baseando-se na Consolidação das Leis Trabalhistas (CLT) e das normas constitucionais. Enfatiza algumas normatizações que suscitam dúvidas e conflitos no cotidiano profissional do enfermeiro, tais como: duração da jornada de trabalho, períodos de descanso intra e entre jornadas, horas extraordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
4
0
7
Order By: Relevance
“…Analyzing the weekly working hours of nurses from 2003 to 2010, it is observed that there is growth in the formal labor relationships, whose journey is from 31 to 44 hours (Figure 1). The increase in working hours is also perceived by the accumulation of employment bonds by nurses in order to compensate for the low wages received (Freitas, Fugulin and, Fernandes, 2006). As Figure 1 refers to the journey of a single bond, it can be inferred that nurses are working much more than 40 hours per week due to the accumulation of bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing the weekly working hours of nurses from 2003 to 2010, it is observed that there is growth in the formal labor relationships, whose journey is from 31 to 44 hours (Figure 1). The increase in working hours is also perceived by the accumulation of employment bonds by nurses in order to compensate for the low wages received (Freitas, Fugulin and, Fernandes, 2006). As Figure 1 refers to the journey of a single bond, it can be inferred that nurses are working much more than 40 hours per week due to the accumulation of bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Justificativas para ocorrências de erros de medicações O contexto econômico e político atual interfere na regulação das relações no trabalho e, consequentemente, na política dos recursos humanos das organizações. Os gestores, na tentativa de diminuir seus problemas financeiros, optam por enxugar o número de funcionários, causando assim uma sobrecarga de trabalho aos que ficam (11) . "Sobrecarga de trabalho, às vezes tu tá agitado e tem que fazer.…”
Section: Errosunclassified
“…The nursing personnel sizing is the nurse's responsibility, given her/his direct care practice and ability to assess and identify resources able to meet the demand (7) . Such activity has an initial stage, which consists of forecasting how many employees are necessary per category, so as to meet the demands of nursing care, which is directly or indirectly provided to the clientele (4) .…”
Section: The Problematic Of the Nursing Schedule Elaborationmentioning
confidence: 99%